A survey of triploid block inconsistency: potential mechanisms and evolutionary implications on polyploid speciation - Salony, Susnata; Clo, Josselin; Kolář, Filip; Lafon Placette, Clément (Journal of experimental botany, 2025)
The triploid block, primarily caused by endosperm developmental issues, is known as a significant barrier to interploidy hybridization among flowering plants and, thereby, polyploid speciation. However, its strength varies across taxa, with some instances of leakiness, questioning its universal role as a barrier. We conducted a literature survey to explore the causes of the variation in the strength of the triploid block across 11 angiosperm families. We assessed the impact of interploidy cross direction, types of endosperm development, endosperm persistence at seed maturity, and divergence between cytotypes using a Bayesian meta-analysis. We found a significant influence of the type of endosperm in shaping variation in triploid block strength. Other factors tested had no impact on triploid seed viability, probably due to limited data and inconsistencies in estimation methods across the literature. In addition, triploid seed viability in experimental crosses was sometimes correlated to the occurrence of triploid hybrids in nature, sometimes not, suggesting a mixed role for the triploid block in shaping interspecies gene flow. Altogether, our study highlights the need for unified approaches in future studies on the triploid block to advance our understanding of its variation and evolutionary implications.
Keywords: vznik druhů (genetika); Polyploidy; biologická evoluce; triploidie; Gene Flow; Genetic Speciation; Seeds; Biological Evolution; hybrid seed lethality; semena rostlinná; Endosperm; polyploidy speciation; tok genů; endosperm; Hybridization, Genetic; hybridizace genetická; interploidy gene flow; natural variation; Triploidy; triploid block; Endosperm development; Magnoliopsida; polyploidie